Local variation within marinas: Effects of pollutants and implications for invasive species. (August 2018) - Kenworthy, Joseph M.; Rolland, Guillaume; Samadi, Sarah; Lejeusne, Christophe
Abstract: Urban structures like marinas are dominant features of our coasts, often hotspots for invasive species. The processes that govern the distribution of invasive species within and between marinas are not well understood. We therefore investigated the impacts of local-scale variability within and between marinas, analysing fouling communities at two zones (inner and outer) within three close marinas in accordance with pollutants recorded in the water and sediment. Communities varied between zones, however no significant differences in abundances of invasive species was recorded. The inner zones contained higher levels of copper and other pollutants and were correlated with lower biodiversity and abundances of many species in comparison to the outer zones. Only the native Ascidiella aspersa was found in greater abundances in the inner zones. This local-scale variability and how it impacts biodiversity is important for consideration for coastal managers in mitigating the build-up of pollutants and spread of invasive species. Highlights: Community surveys were performed analysing within and between marina variability. A combined approach using macromorphology, microscopy and molecular methods Fouling communities significantly differ between inner and outer zones of marinas. Diversity was adversely affected by higher quantities of pollutants in inner zones. Local-scale variability is important for structuring marine fouling communities.